Estrategias de autorregulación del aprendizaje y rendimiento académico de los estudiantes de la carrera de psicopedagogía de la Universidad Nacional de Chimborazo. - Verdesoto Parra, Priscila Elizabeth (2023)
The objective of this research was to establish the level of use of cognitive, metacognitive and resource management self-regulation learning strategies, identifying academic performance and correlating metacognitive self-regulation learning strategies with the academic performance of students of the Psychopedagogy career of the National University of Chimborazo, emphasizing those who are in the first semester. The study started from the assumption that students who have better defined and applied strategies have a higher level in their academic performance. The methodology had a quantitative approach, the psychometric technique was used with the Motivational Questionnaire and Learning Strategies instrument, MSLQ and, also the report card regulated by a quantitative scale, in a range of qualifications. The interpretation of the data was carried out using the Excel program, for the elaboration of statisticians such as: tables and cakes, from the analysis of each question reflected in the test and the qualifications record, obtaining results globally according to the self-regulation strategies used by the students and their academic performance. While for the correlation the SPSS program was used and it was possible to obtain the results based on the objectives proposed at the beginning, discarding the research hypothesis and accepting the null hypothesis, this means that there is no correlation between the study variables.